The effects of sintering temperature on the dielectric properties of Sr(Fe0.5Nb0.5)O3doped with Ba(Zr0.25Ti0.75)O3 - Lalita Tawee (2018)
© 2016 Trans Tech Publications, Switzerland. In this work, ceramics of Sr(Fe0.5Nb0.5O3) doped with Ba(Zr0.25Ti0.75)O3(10 mol%), were synthesized by a solid-state reaction technique. The powders were calcined at 1300 oC for 12 hr and then sintered at 1400-1500 oC for 4 hr. Effects of sintering temperature on the properties of the ceramic were studied. Phase formation, microstructure, and dielectric properties were investigated. The ceramics exhibited a perovskite structure with cubic symmetry. Grain size of the ceramics increased with increasing the sintering temperature. The ceramics exhibited a dielectric relaxation like behavior with high dielectric constants over a wide temperature range.